Mediación como método de solución de conflictos - Galárraga Carvajal, Diego Renato (2024)
In our country, Mediation and Arbilration is a new procedure. Befare the enactment of the Arbration and Mediation Law, all procedures, processes and conticts were handled by ordinary judges, or by offlcials of lhe judiciary system who were in charge of handling and resolving legal disputes. Due to the lack of speed in dispatching cases, in the year 1997 the Law on Arbitration and Mediation was issued. Through it an alternativa mechanism for the parties involved to resolve their public, or prívate legal disputes and conflicts was initiated by going to the Cenlers for Medialion and Arbitration. These helped to produce many positiva results as matters were resolved in an agile and quick manner. It assisted the parties involved to avoid having to take any further legal action; having to go through long tigation processes; and held to avoid paying the normal high cost of all legal procedures.